« On n’aime pas la littérature » : Flaubert et l’institution scolaire - Florence Pellegrini (Flaubert: Revue Critique et Génétique)
This contribution has its origin in the 2019 reform of the high school curriculum and the lists of literary works imposed for the proof of french that it reintroduces. It proposes some reflections on the status of literature in the teaching and on the place and choice of the Nineteenth Century authors — more specifically Flaubert — in the Official Instructions of the French National Education System and in the declensions proposed by school textbooks. In particular, we study the representation of the writer that the School contributes to convey.